Posterior Spinal Surgery for Extradural Spinal Metastasis of Round Cell Tumor in the Lower Thoracal Region - Marleen Marleen; Tjokorda GB Mahadewa; I Wayan Juli Sumadi (Neurologico Spinale Medico Chirurgico, 2020)
Spinal cord dysfunction caused by a spinal tumor is not always easy to treat since the tumor itself possesses variably etiology and low ability of nerve impairment to recover. The most common extradural tumor is derived from metastases, followed by other pathology such as plasmacytoma, lymphoma, etc. Since histopathologically they may present as round cell tumors, pre-operative data and intraoperative findings may help the clinician to establish appropriate diagnosis. This case report aims to describe the role of posterior spinal surgery and the reasoning of the selected approach in the treatment of spinal metastasis mimicking plasmacytoma in the lower thoracal region. We report 56 years old male who has myelopathy symptoms caused by lower thoracal extradural mass lesion, which histopathological study shows round cell tumor findings. Laminectomy and posterior stabilization were undertaken, and additional rotational flap was made to close sacral decubitus ulcer defect. Axial pain was improved and the patient discharged from the hospital with improved quality of life.